Pengaruh Otonomi Keuangan, Akumulasi Surplus dan Sisa Lebih Perhitungan Anggaran (SiLPA) terhadap Perubahan Anggaran Belanja Bantuan Sosial - Randhi Dwi Putra; Fefri Indra Arza (Jurnal Eksplorasi Akuntansi, 2023)
This research aimed to determine the examine the effect of financial autonomy, accumulated surpluses, budget calculation excess on social assistance budget. The population in this research are all Regency/City in Sumatera in 2017-2020. The sampling technique used the purposive sampling. Total sampel are 51 districts with 4 period years. The statistical method used panel data regression analysis. The result showed that financial autonomy, accumulated surpluses, budget calculation excess had a positive effect on social assistance budget.